Potential Analysis Financial Distress On Company Food & Beverage Registered In Bursa Efek Indonesia - Sarphan, Lisdhayanti; Kamaluddin, Murdjani; Nur, Muh. (International Journal of Management and Education in Human Development, 2024)
This study aims to determine the Analysis of Potential Financial Distress in Food & Beverage Companies Listed on the Indonesia Stock Exchange, using financial statement data for the 2019-2023 period. The sample collection technique has been carried out by purposive sampling and 8 companies have been selected as samples. This research is descriptive statistics using the Altman, Springate, and Zmijewski analysis models. The results of this study indicate that the Altman model can predict financial distress, the Springate model can predict financial distress, and the zmijewski model can predict financial distress.